Volunteerism amongst Singaporean undergraduates : a study - Ang, Yi Xin (2013)
This paper aims to tackle the social phenomenon of youth volunteerism – first from a broad point-of-view that examines the issue on a macro-level, and then looking into the inner-workings of youth volunteers to get a sense of their perspectives and their motivations behind engaging in the social activity. The occurrence of volunteerism will be examined under a sociological lens vis-a-vis the sociological modernisation framework to identify the modes of volunteering activity undertaken by local university undergraduates. Understanding volunteerism that’s embedded in the culture of youths on a micro-level is a plausible method in propelling the social phenomena forward. Moreover, research conducted would add to the knowledge reservoir of youth volunteerism in the Singapore context.